Steel Processing Production Process At CV. ABC: Proses Produksi Pengolahan Baja Di CV. ABC - Yulianto, Rizky; Putra, Boy Isma (Universitas Muhammadiyah Sidoarjo, 2024)
The production process is a way, method and technique for creating or increasing the usefulness of a good or service using existing resources (labor, machines, materials, funds). CV. ABC is a company that focuses on the steel processing industry sector. This company's specialization includes making various products, such as fences, canopies, stairs, and building structures such as warehouses and housing. The purpose of carrying out this activity is to observe the production process of making fences and analyze the production process using a production process map (Operation Process Chart) and Bill of Materials. Based on field observations using the production process map at CV. It can be seen from Tiga Karya Persada Indonesia that making 1 fence takes a total of 795 minutes, consisting of 6 operational processes with a total time of 630 minutes and there are 8 inspection processes with a total time of 165 minutes.